The problem of research abilities among the students of higher pedagogical educational establishments - Цун, Чжоу (Pedagogy of Higher and Secondary Education, 2014)
Chzhou Tsun. The problem of research abilities among the students of higher pedagogical educational establishments The article presents the analysis of the formation of research skills among students of higher pedagogical educational institutions.